Leo Strauss on science : thoughts on the relation between natural science and political philosophy - Minkov, Svetozar, 1975- (SUNY series in the thought and legacy of Leo Strauss., 2016)
Drawing upon a wealth of previously unpublished archival material, Leo Strauss on Science brings to light the thoughts of Leo Strauss on the problem of science. Introducing us to Strauss's reflections on the meaning and perplexities of the scientific adventure, Svetozar Y. Minkov explores questions such as: Is there a human wisdom independent of science? What is the relation between poetry and mathematics, or between self-knowledge and theoretical physics? And how necessary is it for the human species to exist immutably in order for the classical analysis of human life to be correct? In pursuing these questions, Minkov aims to change the conversation about Strauss, one of the great thinkers of the past century.